Self Audit as part time Fistula Surgeon - Abdullah, Aziz (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the outcome of all the patients operated by single surgeon during this period. Methods: From 2006 to2017 total of 2870 patients were operated. These included all cases of urinary and fecal incontinences, inclusive of both acquired and congenital disorders like cloacal abnormalities and bladder exstrophy. Total 2460 cases of Vvf were operated out of which around 68% were operated via vaginal route remaining were via abdominal routes. Abdominal approach was also used for all cases of ureteric reimplantation and vesico uterine fistula. Total of 5 cases of fecal incontinence with cloacal presentation, all of them were older than 16 years. There were five cases of untreated cases bladder exstrophy all adult females treated with Mitroffnof procedure and bladder augmentation. Of fecal incontinence there were 340 cases out of which 190 cases were of 4th degree tear all of them were operated in similar manner. Around 210 cases of ureteric injury were treated. 10% of them were amenable to endoscopic intervention while remaining were reimplanted. Results: Over all successful closure of fistula was around 95.14%. Unfortunately restoration of continence rate was around 82%. This was mostly because of small capacity of bladder, OAB, Stress Incontinence because of damage to pelvic floor and to the urethra. While overall mortality was 2 patients and these attributed to cardiac causes. Over successive years there is decrease in cases due to obstetrical causes but rise in iatrogenic causes. Though number of cases treated remains same. Conclusions: Overall results are good with reasonable results. Though need further input in trainng of surgeon and midwifes for prevention of fistula. Keywords: audit, fistula, surgeon